Activation and self-inactivation mechanisms of the cyclic oligoadenylate-dependent CRISPR ribonuclease Csm6 - Carmela Garcia-Doval (Nature Portfolio, 2020)
Upon target RNA recognition, type III CRISPR-Cas systems produce cyclic oligoadenylates that activate effectors such as Csm6 ribonucleases. Here, Garcia-Doval et al. show that Enteroccocus italicus Csm6 degrades its cyclic hexa-AMP activator, and report the crystal structure of the protein bound to an activator mimic.